2014
DOI: 10.1007/s00345-014-1242-4
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes between open and robotic-assisted radical cystectomy: a propensity score matched analysis

Abstract: ORC and RARC represent effective surgical approaches for the treatment of bladder cancer. Histopathologic outcomes for RARC compare favorably to ORC with respect to soft tissue margin rates and lymph node yield. These data suggest that RARC is an acceptable surgical approach for treatment of bladder cancer that can achieve outcomes that are equal or superior to those of ORC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The characteristics of included studies are summarized in Table 1 . As for urinary diversion, sixteen adopted the extracorporeal method [ 6 , 7 , 9 17 , 20 , 22 25 ]. Similar neobladders were reconstructed between RARC and ORC groups (131 of 593 vs 125 of 654 in thirteen studies [ 6 , 7 , 9 14 , 16 , 17 , 23 25 ] (p = 0.08).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of included studies are summarized in Table 1 . As for urinary diversion, sixteen adopted the extracorporeal method [ 6 , 7 , 9 17 , 20 , 22 25 ]. Similar neobladders were reconstructed between RARC and ORC groups (131 of 593 vs 125 of 654 in thirteen studies [ 6 , 7 , 9 14 , 16 , 17 , 23 25 ] (p = 0.08).…”
Section: Resultsmentioning
confidence: 99%
“…Since then, especially in the latest 5 years, RARC has gained its popularity and achieved decent long-term oncologic outcomes [ 4 , 5 ]. As to comparative analysis of complication rates and perioperative outcomes between RARC and ORC, different studies showed controversial results [ 6 – 20 ]. In 2012, Li et al [ 21 ] conducted a systematic review of literatures, with a meta-analysis of the results to compare RARC with ORC.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, radical cystectomy (RC) with bilateral pelvic lymphadenectomy is the primary treatment for patients with muscle‐invasive bladder cancer (BC) or refractory, high‐grade Ta, T1, Tis BC. To date several contemporary, single centre series of patients treated with RC for BC combined with bilateral lymphadenectomy have been published . However, very few report disease‐specific survival (DSS) as an endpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies report similar oncological outcomes at 5 years for robotic RC compared to open RC. [37383940] Oncological outcomes have been subject to heavy criticism because of selection bias. [4142] However, multiple studies have reported advanced pathology treated with robotic RC has similar oncological outcomes to advanced pathology treated with open RC.…”
Section: Advances In Surgery For Muscle Invasive Bladder Cancermentioning
confidence: 99%
“…[4142] However, multiple studies have reported advanced pathology treated with robotic RC has similar oncological outcomes to advanced pathology treated with open RC. [3738394041] In addition, there is no difference in lymph node yield between the two modalities. [43]…”
Section: Advances In Surgery For Muscle Invasive Bladder Cancermentioning
confidence: 99%